2018
DOI: 10.18203/2320-6012.ijrms20183651
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of ratio of amylose and amylopectin as indicators of glycemic index and in vitro enzymatic hydrolysis of rice and wheat starches

Abstract: Background: Wheat and rice form the staple food of large majority of the population throughout the world. Starch is a carbohydrate which is a homopolymer consisting of a large number of D-glucose units joined by α- glycosidic bonds. Starch can be separated into two fractions-amylose and amylopectin. Amylose, Amylopectin ratio is an indicator of Glycemic Index. Starches with lower amylose content will have higher glycemic indexes. Invitro digestion of starch provides efficient means of analysing carbohydrate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Xie et al [ 85 ] showed significant differences in the starch isolated from wheat bran, as compared to the rest of starch in wheat. A lower amylose content in WB starch might explain the lower GI found [ 86 ], as compared to WG.…”
Section: Resultsmentioning
confidence: 99%
“…Xie et al [ 85 ] showed significant differences in the starch isolated from wheat bran, as compared to the rest of starch in wheat. A lower amylose content in WB starch might explain the lower GI found [ 86 ], as compared to WG.…”
Section: Resultsmentioning
confidence: 99%
“…The amylose-amylopectin ratio is a Glycemic Index indicator. Glycemic indices will be greater in starches with reduced amylose concentration [28].…”
Section: Discussionmentioning
confidence: 99%
“…Starch consists of a mixture of two polymers: amylose (linear chain) and amylopectin (branched chain) (Tester et al 2004). Natural starches consist of about 10%-30% amylose and 70%-90% amylopectin [28]. Hence, the percentage of amylopectin in rice grain was calculated as the given formula.…”
Section: Amylose and Amylopectinmentioning
confidence: 99%
See 1 more Smart Citation
“…Amylose content in common wheat cultivars was determined to be on average 16.91% by Valková et al, (2021) [57]. In comparison to Murugadass and Dipnaik (2018) and Imanningsih (2012) [58,59], who reported values of amylose of 12.7% and 10.2% in wheat starch, respectively, The amylose content (w/w, %) of the starches in the flour samples evaluated in this study, ranged between 20.65 ± 0.03 (C0) and 24.22 ± 0.14 (S1), as shown in Figure 4. Amylose content in common wheat cultivars was determined to be on average 16.91% by Valková et al, (2021) [57].…”
Section: Determination Of the Amylose And Amylopectin Contents In Starchmentioning
confidence: 99%